Antimicrobial use and antimicrobial resistance in broiler farms in peri-urban Wakiso, Uganda - Mbatidde, Irene; Ndoboli, Dickson; Ayebare, Dreck; Biryomumaisho, S.; Roesel, Kristina; Dione, Michel M.; Muloi, Dishon M.; Tenhagen, B.-A.; Wampande, E.; Olsen, J.E.; Moodley, Arshnee (International Livestock Research Institute, 2022)
Objective: A cross sectional study was carried out to 1) describe the antimicrobial use patterns among poultry farmers in Wakiso 2) establish resistant profiles of Salmonella, E. coli and Enterococci among poultry farms in Wakiso. Methods: A cross sectional study in Wakiso district was carried out in October and November 2021 for a period of 6 weeks. A semi structured questionnaire was used to collect data on antimicrobial use on the farms. Boot sock sampling was used to collect samples from the whole poultry house. A composite sample of faecal material was also collected from the poultry house. The information on antimicrobial use is being analyzed for descriptive statistics. The faecal samples were cultured in the laboratory for Isolation of Salmonella, E. coli and Enterococci. The Isolates will further be tested to establish their resistant profiles. The composite sample was used to quantify resistant coliforms against cefotaxime and colistin Results: A total of 200 poultry farms in Wakiso were visited, 211 boot sock samples and 211 composite samples were collected. 29.85% of the respondents were male while 70.15% were female.37.38% had attained secondary level of education. There was observed widespread use of antimicrobials on the farms for treatment of different conditions as well as prevention of disease. The most used groups of antibiotics were, Penicillins, Tetracyclines and Aminoglycosides while Sulphonamides were the least used. From the laboratory analysis, out of the 211 samples collected, Salmonella was isolated at a rate of 8.5%, E. coli at 77.3% and Enterococcus at 62.6%. Resistant coliforms to cefotaxime (5I.7%) and colistin (45.5%) were also identified. Conclusion: There are indications of resistant coliforms among poultry farms in Wakiso. This is attributed to the observed continuous use of antibiotics on the poultry farms. There is need to improve antimicrobial use among farmers. Proper diagnosis of conditions is one possible way that will reduce the use of different antibiotics at farm level.